2012
DOI: 10.1111/j.1469-8137.2012.04135.x
|View full text |Cite
|
Sign up to set email alerts
|

Update on sumoylation: defining core components of the plant SUMO conjugation system by phylogenetic comparison

Abstract: SummaryThe conjugation of the small ubiquitin-related modifier, SUMO, to substrate proteins is a reversible and dynamic process, and an important response of plants to environmental challenges. Nevertheless, reliable data have so far been restricted largely to the model plant Arabidopsis thaliana. The increasing availability of genome information for other plant species offers the possibility to identify a core set of indispensable components, and to discover species-specific features of the sumoylation pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 62 publications
2
71
0
Order By: Relevance
“…One striking difference between them is the presence of an insertion consisting of seven repeats of 23 amino acids in PIAL1, but not in PIAL2 (Supplemental Figure 3C). PIAL1 and 2 have potential orthologs in other plants, although some plants have only a single gene, as opposed to the two representatives in Arabidopsis (Novatchkova et al, 2012). Using the SP-RING sequence for alignment, Figure 1C shows a phylogenetic tree, indicating that plants encode three classes of SP-RING containing SUMO ligases.…”
Section: Two Arabidopsis Genes Encoding Putative Sumo Ligasesmentioning
confidence: 99%
See 1 more Smart Citation
“…One striking difference between them is the presence of an insertion consisting of seven repeats of 23 amino acids in PIAL1, but not in PIAL2 (Supplemental Figure 3C). PIAL1 and 2 have potential orthologs in other plants, although some plants have only a single gene, as opposed to the two representatives in Arabidopsis (Novatchkova et al, 2012). Using the SP-RING sequence for alignment, Figure 1C shows a phylogenetic tree, indicating that plants encode three classes of SP-RING containing SUMO ligases.…”
Section: Two Arabidopsis Genes Encoding Putative Sumo Ligasesmentioning
confidence: 99%
“…Sumoylation, the conjugation of the small ubiquitin-related modifier (SUMO) to substrate proteins, is an essential posttranslational modification in plants (reviewed in Novatchkova et al, 2004Novatchkova et al, , 2012Castro et al, 2012;Mazur and van den Burg, 2012;Flotho and Melchior, 2013;Jentsch and Psakhye, 2013;. SUMO activating enzyme (SAE) catalyzes activation of the SUMO carboxyl terminus by formation of a thioester and SUMO transfer to a SUMO conjugating enzyme (SCE).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiment showed that yeast SUMO and human SUMO1 was able to form chains using Lys7, Lys16 and Lys 17 (Col- one active gene for SUMO-E2 (SCE) in A. thaliana, substrate specificity was usually determined by specific E3 ligase or a certain motif within the target proteins. Covalent modification by SUMO requires consensus motif of ψKXD/E (ψ, hydrophobic amino acid; K, lysine; X, any amino acid, D, aspartic acid; E, glutamic acid), while non-covalent binding of SUMO usually determined by SIM (SUMO-interacting Motif) or SBM (SUMObinding Motif) (Novatchkova et al, 2012;Park et al, 2011). Gene expression pattern of RIN13 and RIL1…”
Section: Isoform Specific Sumoylation Of Rin13 and Poly-sumo Chain Fomentioning
confidence: 99%
“…A. thaliana has one pseudogene and one active gene (AtSCE1a; At3g57870) for SUMO E2 enzyme (Novatchkova et al, 2012). To identify potential target proteins for SUMOylation in A. thaliana, a yeast two-hybrid screening using an Arabidopsis SUMO E2 enzyme, AtSCE1a, as the bait was conducted.…”
Section: Identification Of Arabidopsis Sumo E2 Enzyme Interacting Promentioning
confidence: 99%
See 1 more Smart Citation